Radiological Analysis of Unused Donor Lungs: A Tool to Improve Donor Acceptance for Transplantation?. Issue 7 (30th March 2017) - Verleden, S. E.; Martens, A.; Ordies, S.; Heigl, T.; Bellon, H.; Vandermeulen, E.; Van Herck, A.; Sacreas, A.; Verschakelen, J.; Coudyzer, W.; Van Raemdonck, D. E.; Vos, R.; et al.
Abstract : Despite donor organ shortage, a large proportion of possible donor lungs are declined for transplantation. Criteria for accepting/declining lungs remain controversial because of the lack of adequate tools to aid in decision‐making. We collected, air‐inflated, and froze a large series of declined/unused donor lungs and subjected these lung specimens to CT examination. Affected target regions were scanned by using micro‐CT. Lungs from 28 donors were collected. Two lungs were unused, six were declined for non–allograft‐related reasons (collectively denominated nonallograft declines, n = 8), and 20 were declined because of allograft‐related reasons. CT scanning demonstrated normal lung parenchyma in only four of eight nonallograft declines, while relatively normal parenchyma was found in 12 of 20 allograft‐related declines. CT and micro‐CT examinations confirmed the reason for decline in most lungs and revealed unexpected (unknown from clinical files or physical inspection) CT abnormalities in other lungs. CT‐based measurements showed a higher mass and density in the lungs with CT alterations compared with lungs without CT abnormalities. CT could aid in the decision‐making to accept or decline donor lungs which could lead to an increase in the quantity and quality of lung allografts. Abstract : The authors show that CT scanning could aid in the decision to accept or decline donor lungs.